3 - 2.5 = 0.5
shanay rode 1/2 a mile more
hope this helps :)
Answer:
g(f(x)) = 1x² + 1
Step-by-step explanation:
We are given:
f(x) = x² - 1
g(x) = x + 2
And we want to find g(f(x)).
To do this, we substitute f(x) as x in x+2 (the expression that is equal to g(x)), as g(f(x)) is saying that f(x) is the value of x in g(x).
So, this will be:
g(f(x)) = x² - 1 + 2
Simplify
g(f(x)) = x² + 1
In your system, place 1 in front of x² - this is the coefficient of x², and also 1 after that - this is a constant.
Hello
sin ..... | 0° |30°|45°|60°|90°|
...........| 0...| 1..| 2..| 3..| 4..| write numbers
...........| 0...| 1..|√2.| √3 | 2..| take root square
...........| 0...|1/2|√2/2|√3/2|1| divide by 2
...........| 0...|1/2|√2/2|√3/2|1| .....
cos.....| 90°|60°|45°|30°| 0°|
sin (75°)
=sin(30°+45°)=sin 30°*cos 45° +cos 30°*sin 45°
.................... =1/2*√2/2 + √3/2*√2/2
.................... = √2(1+√3)/4
cos 75°
=cos(30°+45°)=cos 30°*cos 45°-sin 30°*cos 45°
=√3/2*√2/2-1/2*√2/2
=√6/4-√2/4=√2/4*(√3 -1 )
$9.75 because one taco is 0.75 and 13 x 0.75 is $9.75
Answer:
$9
Step-by-step explanation:
In this circumstance, 20% off is the original number (40) divided by 5, and that's the answer. I hope this helps!